Two price zones for the German electricity market: Market implications and distributional effects - Jonas Egerer; Jens Weibezahn; Hauke Hermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
We discuss the implications of two price zones, i.e. one northern and southern bidding area, on the German electricity market. In the northern zone, continuous capacity additions with low variable costs cause large regional supply surpluses in the market dispatch while conventional capacity decreases in the southern zone. As the spatial imbalance of supply and load is increasing, the current single bidding area results more often in technically infeasible market results requiring curative congestion management. Additional bidding zones would enable better market integration of scarce transmission capacities in a system exposed to structural regional imbalances. Using a line sharp electricity sector model, this paper analyzes the system implications and the distributional effects of two bidding zones in the German electricity system in 2012 and 2015, respectively. Results show a decrease in cross-zonal re-dispatch levels, in particular in 2015. However, overall network congestion and re-dispatch levels increase in 2015 and also remain high for both bidding zones. Results are very sensitive to additional line investments illustrating the challenge to define stable price zones in a dynamic setting. With two bidding areas, prices in the model results increase in the southern zone and decrease in the northern zone. The average price deviation grows from 0.4 EUR/MWh in 2012 to 1.7 EUR/MWh in 2015 with absolute values being significantly higher in hours with price differences. Stakeholders within zones are exposed to the price deviations to a different extent. Distributional effects are surprisingly small compared to the wholesale price or different network charges.
Keywords: L51; L94; Q41; Q48; 330; German electricity market; congestion management; bidding zone configuration; distributional effects